THE INFLUENCE OF LEADERSHIP AND REMUNERATION ON EMPLOYEE PERFORMANCE WITH WORK DISCIPLINE AS A MEDIATION VARIABLE (STUDY ON SKADRON-31/SERBU SEMARANG) - Yuda Wibawa; Arini Novandalina; Marnoto Marnoto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Performance is a work result achieved by a person in carrying out the tasks given to him which is based on skill, experience, seriousness and time. The purpose of this research is to determine the influence of Leadership and Remuneration on Employee Performance with Work Discipline as a Mediating Variable at Squadron-31/Serbu Semarang. The population in this study was 51 employees at Squadron-31/Serbu Semarang. So that 50 members of the population except the Commander became respondents in this research or saturated sample/Population Study. This research variable uses exogenous variables consisting of Leadership and Remuneration and 2 endogenous variables, namely work discipline as mediation and employee performance. The data collection method uses a questionnaire. Data analysis methods include descriptive statistics and quantitative analysis using SEM-PLS. Based on the results of data analysis, it is concluded that Leadership has no effect on Work Discipline, Remuneration has an effect on Work Discipline, Leadership has an effect on Employee Performance, Remuneration has an effect on Employee Performance, Work Discipline has no effect on employee performance. Suggestions that can be given to future researchers are to conduct research on other organizations with larger samples, so that the research results can be generalized. Apart from that, you can replace the independent variable because there are still other variables that can influence it based on the coefficient of determination